COLONIC MALAKOPLAKIA - Arit Prakash,; Noshaba Noor,; Ayesha Marchant,; Mariam Ghori,; Molani, Rameen (Journal of Ayub Medical College Abbottabad, 2024)
This case report is of a 10-year-old female who presented with complaints of blood in her stool and colicky abdominal pain for the last 1.5 years. Biopsy samples from the rectum and left-sided colon were taken during a colonoscopy, revealing numerous histiocytes having calcified bodies (Michaelis-Gutmann bodies). Diagnosis of Malakoplakia was confirmed with no evidence of dysplasia, malignancy, or granuloma.